Healthcare Facilities Choice for Maternity Care in Indonesia: Do Socioeconomic Factors Affects? - Stefanus Supriyanto; Ratna Dwi Wulandari; Nikmatur Rohmah; Agung Dwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2022)
The government encourages maternity care in health facilities to reduce maternal mortality. The study aims to analyze the impact of socioeconomic factors on healthcare facilities’ choice for maternity care in Indonesia. The study used secondary data from the official report of the Indonesia Ministry of Health. The study takes all provinces as samples. Moreover, the study used the proportion of maternity care in health facilities as a dependent variable. On the other hand, the research analyzed four other variables as independent variables: percentage of the poor population, percentage of the population having health insurance, literacy percentage of population >15 years, and the unemployment rate for population >15 years. The study analyzed the data using a scatter plot. The study results show the lower the poor population in the province, the higher the proportion of maternity care in health facilities in that province. The higher the percentage of the population having health insurance in an area, the higher the proportion of maternity care in health facilities in that area. Meanwhile, the higher the literacy percentage of population >15 years in a province, the higher the proportion of maternity care in health facilities in that province. Moreover, the higher the unemployment rate for population >15 years in a province, the higher the proportion of maternity care in health facilities in that province. The study concluded that the four independent variables analyzed ecologically were associated with maternity care in health facilities.